Canadian Expert Opinion on Breast Reconstruction Access: Strategies to Optimize Care during COVID-19. Issue 2 (February 2022) - Isaac, Kathryn V.; Buchel, Edward W.; Brackstone, Muriel M.; Doherty, Christopher; Lipa, Joan E.; Zhong, Toni; Semple, John L.; Brown, Mitchell H.; Snell, Laura; Mahoney, Mary-Helen; Vorstenbosch, Joshua; Wheelock, Margaret; et al.
Abstract : Background: Breast reconstructive services are medically necessary, time-sensitive procedures with meaningful health-related quality of life benefits for breast cancer survivors. The COVID-19 global pandemic has resulted in unprecedented restrictions in surgical access, including access to breast reconstructive services. A national approach is needed to guide the strategic use of resources during times of fluctuating restrictions on surgical access due to COVID-19 demands on hospital capacity. Methods: A national team of experts were convened for critical review of healthcare needs and development of recommendations and strategies for patients seeking breast reconstruction during the pandemic. Following critical review of literature, expert discussion by teleconference meetings, and evidenced-based consensus, best practice recommendations were developed to guide national provision of breast reconstructive services. Results: Recommendations include strategic use of multidisciplinary teams for patient selection and triage with centralized coordinated use of alternate treatment plans during times of resource restrictions. With shared decision-making, patient-centered shifting and consolidation of resources facilitate efficient allocation. Targeted application of perioperative management strategies and surgical treatment plans maximize the provision of breast reconstructive services. Conclusions: A unified national approach to strategically reorganize healthcare delivery is feasible to uphold standards of patient-centered care for patients interested in breast reconstruction.